2020
DOI: 10.1101/2020.06.29.177469
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population Dynamics and Neuronal Polyploidy in the Developing Neocortex

Abstract: SUMMARYThe mammalian neocortex is composed of different subtypes of neurons which are generated during embryogenesis by sequential differentiation of neural progenitors. While molecular mechanisms that control neuronal production in the developing neocortex have been extensively studied, the dynamics and absolute numbers of the different progenitor and neuronal populations are still poorly characterized. Here we describe a medium throughput approach based on flow cytometry and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 54 publications
(51 reference statements)
0
4
0
Order By: Relevance
“…Modern genetic approaches investigating potential cell cycle re-entry in vertebrate brains began taking shape in the early 2000’s. In recent years, observations of bona fide polyploidy in neurons of the retinal ganglion of the chicken and mouse, cerebral cortex of the rat and neocortex of the mouse have been made using modern flow cytometry and high resolution imaging techniques ( Morillo et al, 2010 ; López-Sánchez and Frade, 2013 ; Ovejero-Benito and Frade, 2015 ; Martin et al, 2017 ; Jungas et al, 2020 ). Work from the Frade lab has shown that the neurons of the retinal ganglion become tetraploid in an E2F-dependent manner.…”
Section: Are All Terminally Differentiated Neurons Permanently Diploid and In G0?mentioning
confidence: 99%
See 1 more Smart Citation
“…Modern genetic approaches investigating potential cell cycle re-entry in vertebrate brains began taking shape in the early 2000’s. In recent years, observations of bona fide polyploidy in neurons of the retinal ganglion of the chicken and mouse, cerebral cortex of the rat and neocortex of the mouse have been made using modern flow cytometry and high resolution imaging techniques ( Morillo et al, 2010 ; López-Sánchez and Frade, 2013 ; Ovejero-Benito and Frade, 2015 ; Martin et al, 2017 ; Jungas et al, 2020 ). Work from the Frade lab has shown that the neurons of the retinal ganglion become tetraploid in an E2F-dependent manner.…”
Section: Are All Terminally Differentiated Neurons Permanently Diploid and In G0?mentioning
confidence: 99%
“…However, this endoreplication program is differentially regulated in chick and mouse central nervous system, as p27 kip1 is necessary for tetraploidization in the chick, but not the mouse RGCs ( López-Sánchez and Frade, 2013 ; Ovejero-Benito and Frade, 2013 , 2015 ). Further advances in imaging and flow cytometry techniques have identified polyploid pyramidal neurons in the cerebrum of the rat, and the neocortex of the mouse, but the function and underlying cause for their polyploidy remain elusive ( Sigl-Glöckner and Brecht, 2017 ; Jungas et al, 2020 ). These studies show sufficient evidence that polyploidization does indeed occur in higher vertebrates, suggesting that neuronal polyploidization may be a well conserved phenomenon.…”
Section: Are All Terminally Differentiated Neurons Permanently Diploid and In G0?mentioning
confidence: 99%
“…To consolidate these data, we also quantified the total number of PAX6+ and TBR2+ cells in Control (Ctl) and CDC25B cKO cortices using cytometry (Jungas et al 2020). While the total number of PAX6+ cells is not modified, the number of TBR2+ cells is significantly reduced in CDC25B cKO at E14.5 confirming that bIP but not aRGs production is affected in CDC25B cKO (Figure 3-figure supplement 1) .…”
Section: Resultsmentioning
confidence: 99%
“…Flow cytometry analysis were conducted as described in (Jungas et al 2020). Cortical hemispheres were collected in PBS-1% FCS and cells mechanically dissociated through a 40-μm nylon mesh (Clearline).…”
Section: Methodsmentioning
confidence: 99%